(3GdahGFO GdMGFQjIs - (3GdHgHgGfj, eMeO GdHgHgGfj, eMeO HGbQ Hf eMeO Cced GdCUagGfj, J (B1205(3g` (B1891(3es ((3GdeTgO GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf MekOG dG jbhi Ydi EMUGFg EdG gh (B... (3aEfg deG HYO GdYgO Yf ReGf GdCFeI Ydjge GdSdGe hNaj EeGQGJ Gdabg hGdCOdIs
(3BNQgG (B:s
(3BNQgG(B: (3ceG hQO GdMOjK aj eYQaI GdfMh hfTGgO aj ZjQgG eY Cf JgPjH GdCNdGb ef ChLH GdCTjGA ceG dG jNai hGddg GdgGOj Edi WQjbg hdG JMUd GdgOGjI EdG HEQTGOgs
(3HBNQgG eSCdI CUhdjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 154s
(3GdPQjYI, L (B16: 235s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis